EFEKTIVITAS ORGANISASI KELOMPOK MASYARAKAT PENGAWAS POKMASWAS DALAM BIDANG PERIKANAN DI DESA BULUH CINA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Refliani "; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Fishery resources are managed in a serious way, it will contribute more to the national economic development and can alleviate the poverty of Indonesian society, especially fishing communities and fish farmers. Therefore, fishery resources must be managed and utilized optimally in order to contribute significantly to the nation's overall development. Increasing intensity of fishery resource utilization will pose a threat to its sustainability. To overcome this problem, there needs to be community involvement in conducting supervisory activities to preserve and preserve fishery resources in their respective regions by establishing a Community Monitoring Group (POKMASWAS) in every region in Indonesia. The type of research used is descriptive with qualitative research approach, data source used in this research include primary data and secondary data, the location of this research is in Buluh China Village Siak Hulu District Kampar regency. Infroman in this research is Head of Fishery Development and Cultivation, Chairman, Secretary, and Pokmaswas member and user. The results of the research indicate that the effectiveness of the organization of the Community Watch Group in this area has not been effective, because the members and management of the organization have not been routinely in performing their duties, and also constrained the facilities, facilities and infrastructure of the organization that have not existed so that the members and management of Pokmaswas organization have not been able to develop the organization in the future.Keywords: Organization Effectiveness, Community Empowerment, Village Development, Pokmaswas.